Symbolika ptaków w "Enarrationes in Psalmos" świętego Augustyna - Cieśluk, Marek (Vox Patrum, 2008)
The article discusses the symbolism of birds and shows how Augustine in his work "Enarrationes in Psalmos" uses in his pastoral work the appearing in the text references to such the birds: eagle, hen, pelican, tawny owl, sparrow and turtle dove. In explaining the texts of the Psalms, Augustine tries to relate their symbolic meanings, if possible, to Christ. In all the analyzed passages, we can see Bishop Hippo as a pastor who not only tries to explain the difficult texts of the Old Testament based on his knowledge, but also makes efforts that they best influence the Christians.